ANALISIS STRATEGI PENGEMBANGAN USAHA PONDOK PESANTREN DALAM UPAYA MEWUJUDKAN KEMANDIRIAN EKONOMI PESANTREN: Studi Kasus pada Bidang Usaha (BIUS) Pondok Pesantren Salafiyah Syafi’iyah Sukorejo - Anwar, Zainul; Sholiha, Imroatus (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
This research wants to know the business development strategies carried out by the Sal-Saf Sukorejo boarding school business sector in an effort to realize the Islamic boarding school's economic independence and what obstacles are faced in developing the business. This type of research is field research with a qualitative descriptive approach, obtaining research results, business development strategies carried out by expanding the business scale through investment, increasing production, and developing the business in other places. Expanding business scope. Carry out structured financial management. Strengthen marketing. Provide extra assistance to newly opened units. As well as carrying out product innovation. With the strategy implemented, the Islamic boarding school can achieve economic independence, because the business sector does not have consumer debt, has business confidence, has investment, is able to manage cash flow, and is mentally strong when facing financial disruption. Meanwhile, the obstacle faced in developing a business is a lack of understanding by human resources about business development strategies so that regular training and evaluation is required. However, these obstacles can still be overcome with intense monitoring and controlling.